Impact of Aging on Urinary Natriuretic Peptides in Nocturia and Nocturnal Polyuria - Lakshay Khosla; Joseph U. Boroda; Joshua Salama; Syed N. Rahman; Danielle J. Gordon; Matthew W. Moy; Yonatan Akivis; Alla Akivis; Jason M. Lazar; Jeffrey P. Weiss; Lori A. Birder (International Neurourology Journal, 2022)
Purpose The pathophysiology of nocturia and nocturnal polyuria (NP), conditions that become more prevalent with aging, may in part be explained by changes in hormones involved in water homeostasis. The purpose of this study was to analyze the impact of aging on urinary natriuretic peptides in nocturia and NP. Methods Patients aged ≥18 years completed 24-hour bladder diaries for assessment of nocturia and NP. They were divided into subgroups of ≥65 years old and <65 years old. Urine samples were collected and analyzed for natriuretic peptide (NT-proANP, NT-proBNP, and NT-proCNP) levels. Peptide levels were compared between patients with and without nocturia/NP and within age subgroups; correlation to the NP index (NPi) was determined. Results Compared to patients without nocturia (N=15), patients with nocturia (N=36) had higher median levels of urinary NT-proANP (15.8 pmol/mmol Cr vs. 10.9 pmol/mmol Cr, P=0.016) and NT-proBNP (6.3 pmol/mmol Cr vs. 4.5 pmol/mmol Cr, P=0.021), but showed no differences in NT-proCNP (2.4 pmol/mmol Cr vs. 2.5 pmol/mmol Cr, P=0.967). Patients ≥65 years old with nocturia had higher NT-proANP (29.8 pmol/mmol Cr vs. 11.0 pmol/mmol Cr, P<0.001) and NT-proBNP (9.6 pmol/mmol Cr vs. 5.0 pmol/mmol Cr, P<0.001) than patients <65 years old. Additionally, patients with NP (N=30) showed higher urinary NT-proANP (19.6 pmol/mmol Cr vs. 10.5 pmol/mmol Cr, P<0.001) and NT-proBNP (6.7 pmol/mmol Cr vs. 4.7 pmol/mmol Cr, P=0.020) compared to patients without NP (N=21). NP patients ≥65 years had higher NT-proANP (29.8 pmol/mmol Cr vs. 12.5 pmol/mmol Cr, P<0.001) and NT-proBNP (9.6 pmol/mmol Cr vs. 4.4 pmol/mmol Cr, P=0.004) than patients <65 years old. NPi positively correlated with urinary NT-proANP (RS=0.417, P=0.002) and NT-proBNP (RS=0.303, P=0.031), but not with NT-proCNP (RS=-0.094, P=0.510). Conclusions Since urinary NT-proANP and NT-proBNP were greater in aged patients with nocturia and NP, natriuretic peptides may contribute to the pathophysiology of these conditions and further research should aim to explore them as targets for management.